Analytical Surveys of Stonehenge and its Environs, 2009–2013: Part 2 – the Stones. (23rd March 2015) - Field, David; Anderson-Whymark, Hugo; Linford, Neil; Barber, Martyn; Bowden, Mark; Linford, Paul; Topping, Peter; Abbott, Marcus; Bryan, Paul; Cunliffe, Deborah; Hardie, Caroline; Martin, Louise; et al.
Abstract : Non-invasive survey in the Stonehenge 'Triangle', Amesbury, Wiltshire, has highlighted a number of features that have a significant bearing on the interpretation of the site. Geophysical anomalies may signal the position of buried stones adding to the possibility of former stone arrangements, while laser scanning has provided detail on the manner in which the stones have been dressed; some subsequently carved with axe and dagger symbols. The probability that a lintelled bluestone trilithon formed an entrance in the north-east is signposted. This work has added detail that allows discussion on the question of whether the sarsen circle was a completed structure, although it is by no means conclusive in this respect. Instead, it is suggested that it was built as a façade, with other parts of the circuit added and with an entrance in the south. RÉSUMÉ: Prospection analytique de Stonehenge et de ses environs, 2009–2013: deuxième partie, les pierres, de David Field, Hugo Anderson-Whymark, Neil Linford, Martyn Barber, Mark Bowden, Paul Linford et Peter Topping Une prospection non-invasive dans le 'Triangle' de Stonehenge, à Amesbury, Wiltshire, a mis en lumière un certain nombre de vestiges qui ont une portée significative sur l'interprétation du site. Il se peut que des anomalies géophysiques indiquent la présence de pierres ensevelies, ce qui renforce la possibilité de présence d'anciens arrangements de pierres, tandis que des lasers scanneurs ont révélé des détails sur la manière dont les pierres avaient été taillées, certaines sculptées plus tard avec des symboles de haches et de poignards. La probabilité qu'un trilithe de pierre bleue avec linteau constituait une entrée au nord-est est indiquée. Ces travaux ont ajouté des éléments qui permettent de discuster de la question de savoir si le cerle de grès Sarsen était une structure complète, bien qu'ils ne soient en aucun cas concluants sur ce sujet. Au lieu de cela, nous proposons qu'il avait été construit comme façade, d'autres parties du circuit ayant été ajoutées, ainsi qu'une entrée au sud. ZUSSAMENFASSUNG: Analytische Surveys von Stonehenge und seiner Umgebung, 2009–2013: Teil 2, die Steine, von David Field, Hugo Anderson-Whymark, Neil Linford, Martyn Barber, Mark Bowden, Paul Linford und Peter Topping Nicht-invasive Untersuchungen im Stonehenge-"Dreieck", Amesbury, Wiltshire, ließen mehrere Befunde erkennen, die für die Interpretation des Ortes von Bedeutung sind. Geophysikalische Anomalien dürften die Position verborgener Steine anzeigen, was die Möglichkeit älterer Steinanordnungen wahrscheinlicher werden lässt, während Laserscans Details liefern zur Art und Weise, in der die Steine zugerichtet wurden, von denen einige später mit Axt- und Dolch-Symbolen versehen wurden. Die Wahrscheinlichkeit, dass ein mit Sturz versehener Blaustein-Trilith einen Eingang im Nordosten formte, wird angezeigt. Diese Arbeiten erbrachten weitere Details, die eine Diskussion der Frage erlauben, ob der Kreis aus Sarsensteinen eine vervollständigte Struktur bildete, obwohl sie in dieser Hinsicht keineswegs abschließend ist. Stattdessen wird angeregt, dass der Kreis als Fassade gebaut worden war, mit weiteren angefügten Teilen des Umlaufs und einem Eingang im Süden. RESUMEN: Prospecciones analíticas de Stonehenge y sus entornos, 2009–2013: parte 2, las -piedras, por David Field, Hugo Anderson-Whymark, Neil Linford, Martyn Barber, Mark Bowden, Paul Linford y Peter Topping La prospección no invasiva del 'Triángulo' de Stonehenge, Amesbury, Wilshire, ha puesto de relieve numerosas estructuras de gran relevancia para la interpretación del sitio. Las anomalías geofísicas podrían señalar la posición de piedras sepultadas añadidas a otros posibles acondicionamientos pétreos, al tiempo que el láser escáner ha aportado detalles sobre la manera en la que estas piedras han sido dispuestas, algunas posteriormente grabadas con símbolos de hachas y puñales. Se anuncia la posibilidad de que un trilito adintelado de roca alóctona formara una entrada en el lado noreste. Este trabajo ha aportado detalles que permiten abordar la cuestión de si el 'sarsen circle' ('círculos de los moros') llegó a ser una estructura completa, aunque no existen datos concluyentes al respecto. En lugar de esto, se sugiere que fue construido como fachada, con otras partes añadidas y con una entrada en el sur.